IMPLEMENTASI PENDIDIKAN KARAKTER DI MADRASAH - MURTANDO, MURTANDO (AL-QALAM: JURNAL ILMU KEPENDIDIKAN, 2019)
The emergence of the idea of character education in education is one of the efforts to improve the quality of education. This idea arises because the process of education that has been done has not been fully successful in building a noble berkakarkter Indonesian people, in accordance with religious teachings and noble values of Indonesia. Educational tendencies are more emphasis on cognitive aspects, resulting in the incessant morality in the lives of learners. In addition, current education tends to forget the moral dimension and character in teaching and learning, resulting in learners who are knowledgeable but not able to take advantage of the knowledge learned in everyday life. The purpose of this research is to know the values that are implanted to the students in character education in MA Al-Mubarok Bandar Mataram Lampung Tengah and the implementation of character education in MA Al-Mubarok Bandar Mataram Lampung Tengah. This study is based on the problems of daily student behavior is still not in accordance with the values of characters taught, and character education has not been implemented optimally in routine activities and school culture.